Poligami Perspektif Hermeneutika Hadis: Analisis Sosiologi - Fatimah al-Zahrah (Matan : Journal of Islam and Muslim Society, 2020)
This paper tried to explore the sociological approach in the study of Hadith about polygamy. The discourse regarding the practice of polygamy until now continued to give rise to controversy among the people. The pros and cons of the issue of polygamy have been widely discussed both in literature and social media. In the marriage law in Indonesia which allows polygamy with a number of conditions, it should lead to a reduction in the practice of polygamy. However, the lack of legal firmness and sanctions on some of these conditions makes the community not fully comply with the terms and conditions in force. The author tried to critically review the traditions about polygamy which on the one hand allows and on the other hand also prohibits polygamy. With hermeneutics and social approaches both the pros and cons of polygamy, what will be seen is no longer about the issue of whether or not polygamy is possible, but rather looking for maqashid or moral ideals from the practice of polygamy which will see the implications at this time.